2014
DOI: 10.2298/mpns14s2039p
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of chronic hepatitis C virus infection in elderly patients

Abstract: Sažetak Uvod. Hronična hepatitis C virusna infekcija u starijem životnom dobu nije mnogo proučavana iako se očekuje porast prevalencije ove bolesti u starijoj populaciji. Materijal i metode. U radu su prikazane kliničko-epidemiološke karakteristike hroničnog hepatitisa kod 153 bolesnika starosti 65 i više godina, lečenih na Klinici za infektivne bolesti Kliničkog centra Vojvodine u Novom Sadu. Rezultati. Nešto zastupljenije su bile osobe ženskog pola − 55,55%; hepatitis C virusna infekcija je najčešće otkriven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A previous study reported that patients infected at an older age (>40 years) could have faster progression of liver disease [4]. Unfavorable treatment outcomes of older patients with CHC can be explained by a greater prevalence of comorbid states at old age, as well as higher cumulative exposition to hepatotoxins from the surroundings during their lives [20].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that patients infected at an older age (>40 years) could have faster progression of liver disease [4]. Unfavorable treatment outcomes of older patients with CHC can be explained by a greater prevalence of comorbid states at old age, as well as higher cumulative exposition to hepatotoxins from the surroundings during their lives [20].…”
Section: Discussionmentioning
confidence: 99%